KASIH ALLAH KEPADA SEMUA BANGSA - Lestari Br Silaban; Flesia Nanda Uli Boangmanalu; Anessa Mei Pasaribu; Herdiana Boru Hombing (Jurnal Teologi Injili dan Pendidikan Agama, 2023)
God sent Jonah to warn the people of Nineveh. Nineveh will be overthrown by God because of the great sin they have committed. However, Nineveh had repented to God, so God did not overturn the city and God loved Nineveh. From this incident, the prophet Jonah was angry with God because God loves Nineveh, and Jonah wanted the salvation that God gave only for the Israelites. In the present context, there are also Christians who have the same thoughts as the prophet Jonah, who think that religions other than Christianity are not religions that are loved by God. The purpose of this research is to show that God's love is universal and He forgives the mistakes of all those who repent and to guide the prophet Jonah and Christians who think that God's salvation or love is only for the nation of Israel and Christians is wrong thinking. The research method used is a qualitative research method and a critical historical approach in the text of Jonah 4:1-11 with the steps of literal translation, comparison of literal translations and the Indonesian Bible Institute (LAI). The results of this research are that God has proven that He loves all nations who have returned to their ways and also that God guided the prophet Jonah about his erroneous thoughts, namely through castor trees and caterpillars.